Cartesian product of the extensions of fuzzy soft ideals over near-rings. (23rd December 2021) - Manikantan, T.; Ramkumar, S.
In this paper, the notions of fuzzy translation, fuzzy multiplication and fuzzy magnified translation of the cartesian product of fuzzy soft sets are introduced. The cartesian product of the extensions of fuzzy soft sets over a near-ring is defined. Using these notions, the concepts of fuzzy soft near-ring and fuzzy soft ideal over a near-ring are studied. Finally, the fuzzy translation, fuzzy multiplication and fuzzy magnified translation of the cartesian product of the extensions of two fuzzy soft sets over a regular commutative near-ring are equivalent for a fuzzy soft near-ring (resp. ideal) is proved.